2015
DOI: 10.1002/jcsm.12025
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional screening is strongly associated with overall survival in patients treated with targeted agents for metastatic renal cell carcinoma

Abstract: BackgroundAlthough commonly observed, malnutrition is poorly characterized and frequently underdiagnosed in patients with metastatic renal cell carcinoma (RCC). The ability of nutritional screening tools to predict overall survival (OS) in patients with RCC has not been adequately validated. The objective of this study was to investigate the performance of nutritional screening tools and their additional prognostic value in patients with metastatic RCC treated with targeted therapies.MethodsPatients were prosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
65
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 27 publications
1
65
0
1
Order By: Relevance
“…Nutritional screening is critically important in order to identify patients in greatest need of nutritional therapy. This is further emphasized by recent findings that highlight the strong association between nutritional screening and survival prediction in oncology populations 71. In the USA, universal screening and assessment of malnutrition in hospitalized patients is mandatory within 24 h of admission 23, 24…”
Section: Discussionmentioning
confidence: 99%
“…Nutritional screening is critically important in order to identify patients in greatest need of nutritional therapy. This is further emphasized by recent findings that highlight the strong association between nutritional screening and survival prediction in oncology populations 71. In the USA, universal screening and assessment of malnutrition in hospitalized patients is mandatory within 24 h of admission 23, 24…”
Section: Discussionmentioning
confidence: 99%
“…In addition to sarcopenia and cachexia, other factors such as muscle attenuation have been shown to independently predict toxicity in gastrointestinal cancer . Although some studies have shown an association between performance status and nutritional screening tools in the prognosis of oncology patients, the studies did not show associations of these parameters with toxicities during chemotherapy. Thus, this study aimed to investigate which parameter of body composition, namely, low muscle mass or muscle attenuation, the presence of cachexia, nutritional status, or functional capacity, better predicts toxicity during chemotherapy in gastrointestinal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…35, 36, 55 However, polypharmacy was not consistently included as part of the GA, which may be due to studies showing mixed results in the correlation between polypharmacy and various clinical outcomes, compared to strong correlations noted in other GA domains such as comorbidities, functional and nutritional status. 33, 56-59 For studies that did include medication assessment, the data was often analyzed and presented as number of medications. For example, Joly at al.…”
Section: Introductionmentioning
confidence: 99%